Improving Catalytic Activity and Reversing Enantio‐Specificity of ω‐Transaminase by Semi‐Rational Engineering en Route to Chiral Bulky β‐Amino Esters. Issue 15 (17th June 2021) - Wang, Yingang; Feng, Jinhui; Dong, Wenyue; Chen, Xi; Yao, Peiyuan; Wu, Qiaqing; Zhu, Dunming
Abstract: The application of wild‐type ω‐transaminase was limited by steric hindrance towards bulky substrates, therefore improvement of the catalytic efficiency and stereoselectivity toward substrates with two bulky substituent adjacent to the carbonyl is of general interest. In this study, according to the double substrate binding pocket theory, a ( S )‐selective ω‐transaminase from the Burkholderia vietnamiensis G4, which showed puny catalytic activity toward the β‐keto esters with small steric hindrance, was engineered to accept bulky β‐keto esters, which were not accessible by any wild‐type enzyme. A few desired variants were obtained that exhibited activity toward bulky β‐keto esters. Furthermore, a substrate‐dependent shift in enantio‐preference of HBV variant towards β‐keto esters with linear or branched aliphatic substituents was observed. The best variant was applied to the asymmetric synthesis of aliphatic β‐amino acids at semi‐preparative scale with high yield and enantioselectivity. This study will improve the general understanding and inspire further engineering work for reversing enantio‐specificity of ω‐transaminases. Abstract : Asymmetric synthesis : A ( S )‐selective ω‐transaminase from the Burkholderia vietnamiensis G4 was engineered for the asymmetric synthesis of bulky β‐amino esters, meanwhile, a substrate‐dependent shift in enantio‐preference was observed towards β‐keto esters with linear and branched aliphatic substituents.